One-Year Trajectories of Diabetes, Hypertension, and Dyslipidemia after Coronary Artery Disease: A Sex-Stratified Retrospective Cohort Study from Kerala, India - Ambili PV; Punitha VC; Sreelal TP; Shankar K; Roy D, Dinesh; Jiju JS; William, Arun; Jayapal V; Abhijith MS; Beegam M, Meena (National Journal of Community Medicine, 2026)
Background: Cardiovascular diseases remain the leading cause of global mortality, with post-CAD cardiometabolic risk factor control frequently suboptimal, particularly among women. This study analysed sex-specific trajectories of diabetes, hypertension, and dyslipidemia one year after CAD in Kerala, India, and exploratorily examined associations with environmental and lifestyle factors. Methods: A cross-sectional study with retrospective baseline ascertainment was conducted among 420 CAD survivors. McNemar's test compared paired pre- and post-comorbidity status within each sex group, while chi-square test assessed sex differences in trajectory distributions. Results: Substantial resolution of baseline risk factors was observed at one year, with diabetes, hypertension, and dyslipidemia resolving in 36.7%, 39.3%, and 36.7% of participants respectively. New-onset comorbidities were equally frequent at 24%, 21.9%, and 18.8% respectively. Exploratory analyses suggested associations between self-reported environmental exposures and specific diabetes trajectories. Conclusions: One-year post-CAD, considerable proportions experienced resolution of cardiometabolic conditions, while comparable subsets developed new or persistent comorbidities. Women showed higher persistent dyslipidemia. Environmental and lifestyle associations identified warrant prospective investigation.